OPTIMIZATION OF SUSPENSION SYSTEM RE-DESIGN ON MINI STRUCTURES BUSES USING SIMULINK FACILITIES - Cep Yudi Hamdani; Yohanes Dewanto (Magister Teknik Mesin Universitas Pancasila, 2026)
The construction of the Bogor–Cianjur–Sukabumi (BOCIMI) Toll Road represents a strategic government initiative to enhance regional connectivity in West Java, reduce congestion in the Greater Jakarta (Jabodetabek) area, and promote the growth of industrial zones, tourism, and satellite cities. Along with the development of toll road infrastructure, the demand for public transportation modes that are both efficient and comfortable has become increasingly important. However, existing road-based public transportation still faces limitations, particularly in terms of ride comfort and vehicle dynamic performance. Therefore, the development and re-design of medium buses with improved comfort through suspension system optimization is required. This study focuses on the modeling and optimization of the suspension system of a PO. Marita medium bus operating on the Jakarta–Cianjur route via Puncak Bogor, using Simulink-based simulation as a representation of the vehicle’s dynamic system. The objectives of this research include suspension system modeling, analysis of suspension parameters that most significantly affect vehicle dynamic response, optimization of the main suspension parameters, and evaluation of vibration response before and after optimization based on body acceleration RMS, maximum suspension deflection, settling time, and damping ratio (ζ). In addition, vehicle response under cornering and acceleration conditions with various speed levels and mass distributions is also analyzed. The research methodology was carried out in several stages, including literature review, collection of vehicle and road data, determination of initial suspension parameters, mathematical modeling, Simulink modeling, initial condition simulation, vibration response evaluation, optimization of spring stiffness (k) and damping coefficient (c), and comparison of results before and after re-design. The results show that the suspension system was successfully modeled and was able to quantitatively represent the vehicle’s dynamic response. The parameters k and c were found to be the most influential on suspension performance. Optimization increased the damping ratio from approximately ζ ≈ 0.03 to ζ ≈ 0.07, accompanied by a reduction in body acceleration RMS from about 0.38 m/s² to 0.21 m/s², maximum suspension deflection from ±85 mm to ±50 mm, and settling time from 6.0 seconds to 2.5 seconds. Under cornering and acceleration simulations, the optimized suspension system maintained stable and well-controlled responses, making it more suitable for the mountainous road characteristics of the Jakarta–Cianjur route via Puncak Bogor.